EXPLORING THE USE AND TYPES OF FIGURATIVE LANGUAGE - Zahro Qodirova Zafarovna (Web of Journals Publishing, 2024)
This article considered when and how to use figurative language in written and spoken language. The author of the article presented brief information about the six types of figurative language, including simile, metaphor, personification, idiom, symbolism, and hyperbole. Some examples of these types were also analyzed.
Keywords: Figurative language, literal language, simile, metaphor, personification, idiom, symbolism, hyperbole.